2008
DOI: 10.1523/jneurosci.1586-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Thalamic Firing Synchrony during Repetitive Whisker Stimulation

Abstract: Thalamic firing synchrony is thought to ensure selective transmission of relevant sensory information to the recipient cortical neurons by rendering them more responsive to temporally correlated input spikes. However, direct evidence for a synchrony code in the thalamus is limited. Here, we directly measure thalamic firing synchrony and its stimulus-induced modulation over time, using simultaneous single unit recordings from individual thalamic barreloids in the rat somatosensory whisker/barrel system. Employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 40 publications
(71 reference statements)
6
81
0
Order By: Relevance
“…Accordingly, first-spike synchrony among thalamic cells activated by the same stimulus angle was identified as the main factor that determines the angular tuning of barrel neurons (Temereanca et al, 2008). This is supported by intracellular recording which showed that as direction diverges from the preferred direction vibrissa-evoked EPSPs in barrel neurons decrease in amplitude and increase in onset latency (Wilent and Contreras, 2005).…”
Section: Rate Code Versus Latency Codementioning
confidence: 74%
“…Accordingly, first-spike synchrony among thalamic cells activated by the same stimulus angle was identified as the main factor that determines the angular tuning of barrel neurons (Temereanca et al, 2008). This is supported by intracellular recording which showed that as direction diverges from the preferred direction vibrissa-evoked EPSPs in barrel neurons decrease in amplitude and increase in onset latency (Wilent and Contreras, 2005).…”
Section: Rate Code Versus Latency Codementioning
confidence: 74%
“…For example, each channel could reflect a different activation mode of subcortical sensory inputs, corresponding to different categories of stimulus events or features. Synchronous thalamocortical activation by strong stimulus events could trigger or modulate slow fluctuations (MacLean et al, 2005;Bruno and Sakmann, 2006;Hasenstaub et al, 2007;Reig and SanchezVives, 2007;Rigas and Castro-Alamancos, 2007;Temereanca et al, 2008;Hirata and Castro-Alamancos, 2010). Meanwhile, finer-scale signals could stem from activation of a smaller fraction of afferents, in response to different, more frequent stimulus events.…”
Section: Different Channels For Input Informationmentioning
confidence: 99%
“…choice probability | neurometrics | psychophysics D etection of a sensory stimulus arises from evoked neural activity starting in the sensory receptors (1) and spanning several subcortical relay stations up to the cortex (2). Previous studies have described the neural activity of relay neurons within the sensory thalamus and its association with cortical activity; however, most of these studies were performed in anesthetized animals (3)(4)(5)(6)(7). Only a few studies have recorded thalamic neural activity from behaving subjects (8)(9)(10)(11).…”
mentioning
confidence: 99%